Use of Coffee Roasting By-Products (Coffee Silverskin) as Natural Preservative for Fresh-Cut Fennel Slices - Miriam Arianna Boninsegna; Alessandra De Bruno; Corinne Giacondino; Amalia Piscopo; Giuseppe Crea; Valerio Chinè; Marco Poiana (Foods)
The coffee roasting by-product, coffee silverskin, represents a serious problem in environmental pollution. Still, it is also an interesting source of chemical compounds that can be recovered and used in the food industry to improve the physical, chemical, and sensory properties of a wide range of food products. This study aimed to evaluate, for the first time, the effect of the coffee silverskin extract (CSE), applied as a dipping treatment, in preserving the storage and the qualitative decay of fresh-cut fennel slices during 14 days of storage at 4 °C. The experimental plan evaluated two dipping solutions (5% and 10%) with coffee silverskin extract and compared them with a conventional dipping in 2% ascorbic acid and a control (water). The use of CSE in the dipping of fresh-cut fennel permitted an increase in the phenolic (chlorogenic and caffeic acids) content for up to 14 days, with good sensory acceptability and physico-chemical and microbiological characteristics. To date, no applications of CSE in this form have been reported, nor has any food by-product extract been investigated for the preservation of fresh-cut fennel, which makes this study a novel contribution to the development of sustainable treatments for minimally processed vegetables.